2001
DOI: 10.1046/j.1439-0531.2001.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross Morphometry of the Bovine Placentome during Gestation

Abstract: Forty-seven pregnant uteri were collected from an abattoir at eight chronological stages of gestation. Assessments were made of placentome number, weight, length shape and ratio of foetal to maternal tissue by weight. The study showed that there was a great variation in number, size, weight and shape of placentomes. There was no significant change in the total number of placentomes during gestation. Both mean weight and length increased significantly during gestation, but there was a significant change in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
30
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 8 publications
(25 reference statements)
15
30
2
6
Order By: Relevance
“…However, placentomes in the African buffalo placenta during all stages examined are clearly distinguishable from placentomes in cattle due to the lack of a caruncular stalk. In cattle, stalk formation regularly occurs from a fetal CRL of 9 cm onwards and includes all placentomes at the end of gestation [29] and [30]. During the period of stalk formation, Björkmann [29] reports the disappearance of the dense cellular layer in the cattle placentome, which is in agreement with the present study.…”
Section: Discussionsupporting
confidence: 90%
“…However, placentomes in the African buffalo placenta during all stages examined are clearly distinguishable from placentomes in cattle due to the lack of a caruncular stalk. In cattle, stalk formation regularly occurs from a fetal CRL of 9 cm onwards and includes all placentomes at the end of gestation [29] and [30]. During the period of stalk formation, Björkmann [29] reports the disappearance of the dense cellular layer in the cattle placentome, which is in agreement with the present study.…”
Section: Discussionsupporting
confidence: 90%
“…UBF remained relatively constant from day 250 through to the day of parturition in previous reports [9,21,22]. In support of this finding, Laven and Peters [17] observed no significant change in the total number of placentomes during gestation and no significant increase in the total weight of placentomes in the pregnant horn after 190 days of gestation. The total blood flow to the gravid uterus is likely maintained or increased by the development of collateral circulation [23], but the ratios of the nongravid to total UBF measured at the uterine artery were unchanged in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Bollwein et al [11] also reported that the volume of blood flow in the uterine arteries ipsilateral to the corpus luteum was higher than that in the contralateral arteries of three cows during gestation. These observations may suggest a diffusion effect, in which the pregnant horn has more and larger placentomes than the nonpregnant horn in cows [17]. The partitioning of total UBF between the fetal and non-fetal horns, as determined by the steady-state diffusion technique, was strongly correlated with the partitioning of the placental mass between the two horns in seven mid-gestation ewes, each carrying a single fetus [18].…”
Section: Discussionmentioning
confidence: 89%
“…Since during pregnancy, all uteri have spare caruncles not covered or attached to a cotyledon (Laven and Peters, 2001), it seems that the number of the buttons that will be used during pregnancy to contribute in the nutrition of the fetus and hence develop toward active placentomes, may be regulated by several factors. Furthermore, in cattle, placentome number is known to be established early in gestation (Neto et al, 2009), and to not change throughout pregnancy (Laven and Peters, 2001). The latter suggests that, during later pregnancy, the bovine fetus cannot respond to greater nutritional demands by forming more cotyledons.…”
Section: Discussionmentioning
confidence: 99%